Court of Fives - Elliott, Kate, 1958- (Elliott, Kate, 1958- Court of Fives novel., 2015)
When a scheming lord tears Jess's family apart, she must rely on her unlikely friendship with Kal, a high-ranking Patron boy, and her skill at Fives, an intricate, multi-level athletic competition that offers a chance for glory, to protect her Commoner mother and mixed-race sisters and save her father's reputation.